Self-reported and measured BMI in Ireland: Should we adjust the obesity thresholds? - David Madden (University College Dublin, UCD School of Economics, 2013)
Using the nationally representative Slan dataset of 2007 we analyse the relationship between self-reported and measured BMI. We find that selfreported BMI significantly underestimates obesity rates and suggest that the traditional threshold of 30 should be adjusted downwards. We outline a number of approaches to choose the optimal threshold and results suggest that the new obesity threshold for self-reported BMI could be as low as 26.
Keywords: 330; body mass index; receiver operating characteristic; sensitivity; specificity